2018
DOI: 10.1111/tra.12565
|View full text |Cite
|
Sign up to set email alerts
|

Rab11 mediates selective recycling and endocytic trafficking in Trypanosoma brucei

Abstract: Trypanosoma brucei possesses a streamlined secretory system that guarantees efficient delivery to the cell surface of the critical glycosyl-phosphatidylinositol (GPI)-anchored virulence factors, variant surface glycoprotein (VSG) and transferrin receptor (TfR). Both are thought to be constitutively endocytosed and returned to the flagellar pocket via TbRab11+ recycling endosomes. We use conditional knockdown with established reporters to investigate the role of TbRab11 in specific endomembrane trafficking path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 63 publications
(138 reference statements)
5
46
0
Order By: Relevance
“…Thus it is likely that VSG en route to the cell surface is subject to proteolysis by TbCatL that has been misdirected into the secretory pathway by TbVps24 ablation (see Figs 3A & 3B). Previously our lab has shown that depletion of the essential housekeeping enzyme ornithine decarboxylase (similar kinetics of silencing and lethality) had no effect on VSG shedding (Umaer, Bush, & Bangs, 2018), confirming that the increase in shedding observed here is related to the knockdown of TbVps24, and not due to a non-specific effect on cell viability.…”
Section: Tbvps24 Silencing Affects Biosynthetic Lysosomal Traffickingsupporting
confidence: 87%
See 4 more Smart Citations
“…Thus it is likely that VSG en route to the cell surface is subject to proteolysis by TbCatL that has been misdirected into the secretory pathway by TbVps24 ablation (see Figs 3A & 3B). Previously our lab has shown that depletion of the essential housekeeping enzyme ornithine decarboxylase (similar kinetics of silencing and lethality) had no effect on VSG shedding (Umaer, Bush, & Bangs, 2018), confirming that the increase in shedding observed here is related to the knockdown of TbVps24, and not due to a non-specific effect on cell viability.…”
Section: Tbvps24 Silencing Affects Biosynthetic Lysosomal Traffickingsupporting
confidence: 87%
“…(Hall et al, 2005). Validated markers for each compartment are: EE, TbRab5A/B (Pal, Hall, Nesbeth, Field, & Field, 2002); RE, TbRab11 Umaer et al, 2018); LE, TbRab7 Silverman et al, 2011), TbRab28 (Lumb et al, 2011), TbVps4 (Silverman et al, 2013), TbVps23 Silverman et al, 2013), and TbVps24 (this work); Lyso, p67 (Alexander et al, 2002) and TbCatL (Koeller & Bangs, 2018;Peck et al, 2008). TbFab1 localizes to both LE and Lyso (Gilden et al, 2017).…”
Section: Data Analysesmentioning
confidence: 76%
See 3 more Smart Citations